Transparencia en la gestión pública en el Perú: Avances al 2021 - Madrid Escobar, Apolinar Junior (2023)
Corruption has been a persistent problem in Peru, and in order to fight it from the public sector, several transparency mechanisms have been implemented with results that are far from what was expected. The objective of this paper is to carry out a theoretical analysis of the most relevant characteristics of transparency in public administration in Peru, for which the main actions developed by the Peruvian State to implement transparency in public administration were reviewed, analyzing their possible influence on the levels of corruption in Peru in the period from 1990 to 2021. As a working method, it was considered appropriate to examine the regulations issued by the Peruvian State, verifying the results obtained in the indicated period. The results show that the measures adopted since the 1990s to institutionalize transparency in the country do not seem to have influenced the level of corruption, thus failing to achieve the goal set in the Plan Bicentenario: Peru al 2021, to position our country as the one with the lowest perception of corruption in all of Latin America. Based on this observation, we conclude that the relationship between transparency and corruption is more complex than commonly believed and requires further research.